Parents' Communication Strategies In Preventing Teenage Promiscuity In Rantau Prapat - Hibriyanti, Silvi; Walisyah, Tengku (Borong Newinera Publisher, 2023)
Effective parental communication tactics play a crucial role in mitigating teenage promiscuity, particularly in the context of Rantau Prapat. This study focuses on the communication tactics employed by parents to address promiscuity and foster positive relationships with their adolescent children, while also being mindful of their social surroundings. The objective of this research is to investigate the communication tactics employed by parents with adolescents, and how parents might guide them to avoid engaging in promiscuous behavior. This research methodology employs qualitative research, specifically field research incorporating direct observation techniques, interviews with a sample of 10 parents (comprising 5 fathers and 5 mothers) who have adolescent children residing in the Torpisang Mata neighborhood. Additionally, the study incorporates documentation studies, drawing upon relevant references and literature. The employed data analysis techniques include data reduction, data presentation, and data retrieval. The findings of this study indicate that there is a presence of transparent and constructive communication between parents and teenagers, which leads to reciprocal support between them. Implementing effective communication skills can foster unity and facilitate meaningful talks within the family. Furthermore, it can mitigate the likelihood of promiscuity by instilling a robust comprehension of morals and Islamic religious principles, so serving as a preventive measure against promiscuity.